2017
DOI: 10.1007/s10068-017-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion, health benefits, and application of ginseng and red ginseng in dairy products

Abstract: Ginseng and red ginseng are popular as functional foods in Asian countries such as Korea, Japan, and China. They possess various pharmacologic effects, including antioxidant, anti-inflammatory, anti-cancer, anti-obesity, and anti-viral activities. Ginsenosides are a class of pharmacologically active components in ginseng and red ginseng. Major ginsenosides are converted to minor ginsenosides, which have better bioavailability and cellular uptake, by microorganisms and enzymes. Studies have shown that ginseng a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 95 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…Microorganisms produce various enzymes, including β-glucosidase, β-glycosidase, β-galactosidase, and l -arabinofuranosidase, which may transform ginsenosides by cleaving the sugar moieties at C–3, C–6, and/or C–20. The transformation pathways for microbial fermentation [ 7 , 62 , 110 ] were as follows: Rb1→Rd→F2→CK; Rb1→Rd→Rg3→Rh2; Rb1, Rb2, Rc→Rd; Rc→Mc→CK; Rb2→compound O→compound Y→CK; Re→Rg2, Rh1; Re→Rg1→Rh1; and Rf→Rh1.…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms produce various enzymes, including β-glucosidase, β-glycosidase, β-galactosidase, and l -arabinofuranosidase, which may transform ginsenosides by cleaving the sugar moieties at C–3, C–6, and/or C–20. The transformation pathways for microbial fermentation [ 7 , 62 , 110 ] were as follows: Rb1→Rd→F2→CK; Rb1→Rd→Rg3→Rh2; Rb1, Rb2, Rc→Rd; Rc→Mc→CK; Rb2→compound O→compound Y→CK; Re→Rg2, Rh1; Re→Rg1→Rh1; and Rf→Rh1.…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%
“…The PPT type consists of an aglycone with a dammarane skeleton and sugar moieties attached to the α-OH at C–6 and/or β-OH at C–20. The oleanane group consists of OA and OT types: The OA type consists of a pentacyclic structure with an aglycone oleanolic acid such as ginsenoside Ro; the OT has an epoxy ring at C–20, and includes majonoside R2 and the pseudoginsenoside F11 (p-F11) [ 7 ]. Moreover, the substituents within the C17 side chains often undergo oxidation, reduction, cyclization, and epimerization, contributing additional diversity in ginsenoside chemical structure [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, consumption of ginseng during pregnancy has been shown to increase the risk of adverse fetal outcomes . In addition, minor side effects of ginseng have been documented, including vaginal bleeding, swelling, diarrhea, breast tenderness, dizziness, tachycardia, insomnia, and headaches . Analysis of the composition of ginseng has disclosed GRb1 as one of the major ginsenoside components, leading to the hypothesis that the adverse side effects are attributable, at least in part, to this saponin compound .…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are a class of pharmacologically active components in ginseng. Major ginsenosides are converted to minor ginsenosides with better bioavailabilty and cellular uptake by steaming to manufacture red ginseng and by treating with microorganisms and enzymes (Park et al, 2010;Jung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consuming yogurt with fruits, vegetables, whole grains, and herbs would assist in increasing intake of nutrients, prebiotics, antioxidants, phytochemicals and dietary fiber and has protective effects against specific diet-related diseases such as diabetes (Fernandez and Marette, 2017). Yogurt supplemented with various products of ginseng and red ginseng has been evaluated for its physicochemical, microbial, and sensory properties by many research groups mainly in Korea (Jung et al, 2017). The research papers showed that addition of ginseng and red ginseng to yogurt base stimulated growth of lactic acid bacteria and enhanced acid production during fermentation and viability of the bacteria during storage of yogurt (Lee and Paek, 2003;Kim and Han, 2005; Bae and Nam, 2006;Kim et al, 2008;Cimo et al, 2013;Hekmat et al, 2013;Jung et al, 2016;Jang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%